Neue Mobilität im ländlichen Raum - Angewandte Elektromobilität - Technologiekonzepte - Mobilitätseffekte. In der Modellregion Elektromobilität Bremen/Oldenburg, kurz NeMoLand, ... von 2011 bis 2014 ; Schlussbericht. - (:unkn) unknown (My University, 2014)
Im Forschungsprojekt wurden Studien und Modelle zur Ausdehnung der Flottenversuche in der Modellregion Bremen/Oldenburg, die Weiterentwicklung von technologischen Ansätzen sowie die Entwicklung bzw. Erweiterung von Verkehrskonzepten im ländlichen Raum erarbeitet.

Urban mobility faces new challenges due to climate change as well as noise and pollution from motorized individual transport. Many cities across Europe have employed bicycle sharing systems as a possible way of addressing these problems. Aside from the direct ecological benefit bicycle sharing systems offer the prospect of novel consumerist routines. Those systems vary in respect to their technical design, their operating models and their respective target audience. Rarely is their operation profitable without public subsidies. It is assumed that a possible risk factor is a high amount private bicycle ownership in the so called cycling cities. This thesis will follow recent studies to first review the current state of the art. The focus will then turn towards the potential of bicycle lending systems in bike cities such as Bremen and the question will be asked whether a bike city could even still exist without a bicycle sharing system. For this purpose several alternative systems are considered for the city of Bremen and subjected to a cost-benefit analysis, in view of the stressed mu-nicipal budget situation. The preferred solution consists of a flexible system using GPS based bicycles but no fixed stations. After collecting and analysing GPS usage data this system might be extended to a hybrid model combining the advantages of flexible and station based systems.
Keywords: Individualverkehr; Mobilität; Verkehrsentwicklung; Ländlicher Raum; Elektroantrieb; Verkehrskonzept; Elektromobilität; Wirtschaftsverkehr